Abundance of arthropods in tree canopies of Banksia woodland on the Swan Coastal Plain - Tassone, R.; Majer, Jonathan (1997)
Canopy arthropods and foliar nutrients were quantified during summer for Banksia menziesii, R. attenuata, B. ilicifolia and Nuytsia floribunda within a low woodland site at Jandakot Airport on the Swan Coastal Plain, Western Australia. Foliar nutrients were higher for N. floribunda than any of the Banksia species. B. ilicifolia differed from the other two banksias in having lower nitrogen and phosphorus but higher potassium. Invertebrate densities were also higher for N. floribunda than any of the Banksia species, while densities on the three Banksia species were relatively similar, albeit with a few predominantly phytophagous taxa having a higher density on B. ilicifolia. These trends provide evidence that, as in other ecosystems where this has been studied, differing arthropod loads between tree species are related to variation in foliar nutrient levels. Tree usage by predominantly insectivorous birds may reflect the relatively low difference in arthropod loads between the three Banksia species and an uneconomic strategy of seeking out low-density N. floribunda trees.